Gendered economic policy making: The case of public expenditures on family allowances - Oznur Ozdamar (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
Parliament is the place where politicians make laws to set the policy direction of countries. Non-involvement of different voices such as gender, race and ethnicity in policy decisions may create an inequality in policy-making. Regarding gender, previous literature suggests that women and men may have different policy prefer- ences and women give more priority to policies related to their traditional roles as care givers to children in the family. Public spending on family allowances is one of the economic policies that plays an important role in helping families for childcare. This paper contributes to the literature by analyzing the relationship between female political representation and public spending on family allowances within a perspective of critical-mass framework.
Keywords: H53; H83; J16; 330; women in economic policy-making; public expenditures on family allowances; critical mass; panel data analysis